2020
DOI: 10.1155/2020/4851671
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Intermittent or Continuous Very Low-Energy Diets in Overweight and Obese Individuals with Type 2 Diabetes Mellitus: A Systematic Review and Meta-Analyses

Abstract: Objective. This study is aimed at investigating the efficacy of a very low-energy diet (VLED) in overweight and obese individuals with type 2 diabetes mellitus (T2DM). Methods. We thoroughly searched eight electronic resource databases of controlled studies concerning the efficacy and acceptability of intermittent or continuous VLEDs in patients with T2DM compared with other energy restriction interventions. Results. Eighteen studies (11 randomized and seven nonrandomized controlled trials) with 911 participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 58 publications
(145 reference statements)
0
6
0
Order By: Relevance
“…[52][53][54][55][56] Dietary Specifics and Types of Diets Remission of T2D requires a sufficient reduction in absorbed calories to decrease adiposity and insulin resistance. 8,[57][58][59] Studies consistently demonstrate that using liquid meal replacements can significantly reduce energy intake and cause weight loss. [59][60][61] For many individuals, however, foodbased approaches are better accepted than liquid meal replacements.…”
Section: Diet and Remission Of T2dmentioning
confidence: 99%
“…[52][53][54][55][56] Dietary Specifics and Types of Diets Remission of T2D requires a sufficient reduction in absorbed calories to decrease adiposity and insulin resistance. 8,[57][58][59] Studies consistently demonstrate that using liquid meal replacements can significantly reduce energy intake and cause weight loss. [59][60][61] For many individuals, however, foodbased approaches are better accepted than liquid meal replacements.…”
Section: Diet and Remission Of T2dmentioning
confidence: 99%
“…51,52 The key to success of lifestyle interventions resides in caloric reduction, as hypocaloric diets were shown to be most effective in terms of weight loss, glycemic control, and effects on liver-related outcomes. [53][54][55] Specific diets, mainly based on modification of macronutrient intake, such as low-carbohydrate, [56][57][58][59][60] very-low-carbohydrate, 57,58,[61][62][63] ketogenic, 62,[64][65][66][67] low-fat, 61,63 low glycemic, high-protein, [68][69][70] meal replacement 71 and vegan diets 61 have proven beneficial effects, but mostly when combined with concomitant energy restriction 72 (Figures 3 and 4; Tables S1 and S2). Mediterranean diets seem to be most effective in improving MASLD, even in the absence of weight loss 73-75 (Table S3).…”
Section: Lifestyle-based Strategies For Reducing Excess Body Weightmentioning
confidence: 99%
“… 46 Similarly, a 2020 systematic review of 18 studies reported that, compared to bariatric surgery, VLEDs offered comparable effects on weight loss, glycemic control, triglycerides, and insulin resistance and suggested that a VLED approach be used for individuals unsuitable or unwilling to undergo surgery. 47 …”
Section: Vleds In Adultsmentioning
confidence: 99%
“…46 Similarly, a 2020 systematic review of 18 studies reported that, compared to bariatric surgery, VLEDs offered comparable effects on weight loss, glycemic control, triglycerides, and insulin resistance and suggested that a VLED approach be used for individuals unsuitable or unwilling to undergo surgery. 47 The findings from the DiReCT study led to the rollout of a VLED program in primary care in the UK, in what was termed a "diabetes remission service". 48 Despite the growing acceptance of the role of a VLED program for weight loss and type 2 diabetes treatment in adults, there remains significant hesitation in their use in youth (see sections, VLEDs in Clinical Practice and Safety of VLEDs in Youth).…”
Section: Vleds In Adultsmentioning
confidence: 99%